Genetic and epigenetic features direct differential efficiency of Xist-mediated silencing at X-chromosomal and autosomal locations - Agnese Loda (Nature Portfolio, 2017)
Xist RNA is required for X chromosome inactivation but it is not well understood how Xist silences some regions more efficiently than others. Here, the authors induce ectopic Xist expression from multiple different X-linked and autosomal loci in cells to explore Xist function.